2022
DOI: 10.15586/aei.v50i6.744
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of DAPK1 attenuates IL-1β-induced extracellular matrix degradation and inflammatory response in osteoarthritis chondrocytes via regulating the p38 MAPK-signaling pathway

Abstract: Objective: To reveal the possible effects of death-associated protein kinase 1 (DAPK1) on the progression of osteoarthritis (OA) and the potential underlying mechanism. Methods: The expression of DAPK1 in OA and normal samples and interleukin (IL)-1β-stimulated chondrocytes was analyzed by quantitative real-time polymerase chain reaction and Immunoblot assay. Cell viability, proliferation, and apoptosis in DAPK1-knockdown cells stimulated with IL-1β were detected by 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…16 These observations shed light on novel therapeutic strategies for management of vascular disease. Importantly, the inhibitory effects of curcumol on HASMCs were dose-dependent, and it aso downregulated the protein levels of matrix metalloproteinase-9 (MMP-9) 17 and matrix metalloproteinase-2 (MMP-2), 18 both of which are essential for cell migration. 19 In addition, Western Blot analyses disclosed that curcumol effectively decreased the LC3-II to LC3-I ratio while enhanced the P62 expression in a dose-dependent manner, and they serve as autophagy indicators.…”
Section: Discussionmentioning
confidence: 99%
“…16 These observations shed light on novel therapeutic strategies for management of vascular disease. Importantly, the inhibitory effects of curcumol on HASMCs were dose-dependent, and it aso downregulated the protein levels of matrix metalloproteinase-9 (MMP-9) 17 and matrix metalloproteinase-2 (MMP-2), 18 both of which are essential for cell migration. 19 In addition, Western Blot analyses disclosed that curcumol effectively decreased the LC3-II to LC3-I ratio while enhanced the P62 expression in a dose-dependent manner, and they serve as autophagy indicators.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory cytokine IL-1β promotes the synthesis and release of numerous inflammatory mediators, including COX-2, all of which play a role in chondrocyte dysfunction in progressive OA [26][27][28]. Evidence suggests that blocking the ability of IL-1β to stimulate the production of inflammatory mediators may be beneficial for OA patients [29,30]. In our study, treatment of chondrocytes with IL-1β resulted in a decrease in cell viability and an increase in the expression of COX-2, PG545 was able to attenuate these effects, whereas 3-MA was able to counteract them.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Additionally, the MAPK signaling pathway plays a role in regulating cytokine-mediated signaling pathways, including those that drive inflammation by producing cytokines. 38 Because both SVM-RFE, and RF analyses showed that TLR7 was the top ranked DE-NRGs, we performed a single gene GSEA on TLR7. In GSE55235 and GSE554757, TLR7 was significantly enriched in the Neutrophil extracellular trap formation.…”
Section: Discussionmentioning
confidence: 99%